Dr. Sumeet Bhanot — Deep Plane Facelift — Sarasota - Bhanot, Sumeet (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Sumeet Bhanot, practicing in Sarasota, USA. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003188; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; usa; sarasota